Effects of curcumin-piperine supplementation on systemic immunity in young women with premenstrual syndrome and dysmenorrhea: A randomized clinical trial. (November 2022) - Bahrami, Afsane; Mohammadifard, Mahtab; Rajabi, Zahra; Motahari-Nasab, Mohammadhossein; Ferns, Gordon A.
Highlights: Curcumin decreased the serum IgE levels in women with premenstrual syndrome and dysmenorrhea. Curcumin supplementation could not affect serum IL-10 and IL-12 concentrations. Curcumin did not affect inflammatory markers in women with premenstrual syndrome and dysmenorrhea. Abstract: Introduction: Premenstrual syndrome (PMS) and primary dysmenorrhea (PD) are common gynecological complications and there is evidence that inflammation may be an important factor in their etiology. There is a relationship between PMS and PD with susceptibility to allergic disorders. We aimed to assess the effect of curcumin co-administered with piperine on serum IL-10, IL-12 and IgE levels in patients with PD and PMS. Materials and methods: A sample of 80 patients were recruited to this triple-blind, placebo-controlled clinical trial. Participants were randomly allocated to curcumin (n = 40) and control groups (n = 40). Each participant received one capsule (500 mg of curcuminoid plus piperine, or placebo) daily, from 7 days before until 3 days after menstruation for three consecutive menstrual cycles. Results: Serum IgE, IL-10 and IL-12 levels were quantified by using an ELISA kit. No significant differences were found between the two groups at baseline, including: age, BMI, and dietary intakes ( P > 0.05). Curcumin + piperine treatment was associated with a significant reduction in the mean serum levels of IgE [from 223.6 ± 258.7 IU/mL to 161.3 ± 240.7; P = 0.001]; but there were no significant changes in the placebo group ( P = 0.12). Serum concentrations of IL-10 and IL-12 before and after the trial period did not differ significantly between the two groups ( P > 0.05). Conclusion: Curcumin plus piperine might be have positive effect on serum IgE levels with no significant changes on serum IL-10 and IL-12 in healthy young women with PMS and PD. Studies with higher doses and longer durations of treatment with curcumin are required to confirm these findings.